Harmonizing Tradition and Technology: A Review of Tarannum and Its Prospects in Computing Research - Hapini Awang; Mohd Faiz Mohd Yaakob; Nur Suhaili Mansor; Ramlan Mustapha; Mohd Zaini Bin Zakaria (Journal of Contemporary Social Science and Educati, 2024)
Non-Indexed Publication